THE GOTHIC ELEMENTS IN TWILIGHT MOVIES: A MODERN INTERPRETATION OF GOTHIC LITERATURE - Apriliani, Nanda; Puspasari, Atika (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research is motivated by the popularity of the Twilight (2008) film, which not only became a global popular culture phenomenon but also demonstrates the revival of key elements of the Gothic literary tradition in a modern form. As an adaptation that combines teenage romance with an atmosphere of darkness and mystery, the film is significant to study within the framework of Gothic literature because it illustrates how classical traditions are transformed in contemporary media. This research aims to (1) identify and analyze the Gothic elements contained in the Twilight film as well as its adaptation of the classical Gothic literary tradition, and (2) explore how the film represents the main Gothic themes of forbidden love, death, and identity in a modern context. This study employs a descriptive qualitative method with content analysis, utilizing the theoretical framework of classical and modern Gothic literature as described by Wolfreys, Robbins, and Womack (2013), Spooner (2006), as well as previous related studies. The research data were obtained from dialogue excerpts, narratives, and visual elements in the Twilight film that contain Gothic elements. The analysis shows that Twilight adapts the core elements of classical Gothic literature namely forbidden love, death, and identity into a modern narrative context. These themes are represented through Bella and Edward’s cross-world romance, the reinterpretation of death as sacrifice, and the characters’ identity crises, all framed in the emotional language of contemporary youth. Supported by visual aesthetics such as dim lighting, fog, and isolated forest landscapes, the film bridges the classical Gothic tradition with 21st-century sensibilities.